Comparative Evaluation of Modified Giemsa and Warthin-Starry Stains for Helicobacter pylori Detection and Density Grading Using the Updated Sydney System - Firmansyah, Rahman; Miskad, Upik Andriani; Cangara, Muhammad Husni; Wahid, Syarifuddin; Juanita, Juanita; Tawali, Suryani; Yamin, Amalia (Asian Pacific Journal of Cancer Biology, 2025)
Objective: Helicobacter pylori is one of the main causes of chronic gastritis, gastric ulcers, and stomach cancer. Accurate diagnosis of H. pylori infection is essential for effective treatment and prevention. Methods: This research is an analytical observational study with a cross-sectional retrospective design that aims to compare histochemical special stains, Modified Giemsa, and Warthin-Starry for H. pylori Detection and Density Grading using the Updated Sydney System in 150 gastric biopsies of Chronic Gastritis at the Department of Anatomical Pathology, Dr. Wahidin Sudirohusodo General Hospital, Makassar, Indonesia. Result: There was a significant difference in detection of H. pylori (p=0.001), Warthin-Starry detected more H. pylori positive 111 samples (74.00%) than Modified Giemsa positive 95 samples (63.30%) and there was a significant difference in Density Grading using the Updated Sydney System (p=0.001), Warthin-Starry staining showed a higher density score of Grade 2 (moderate) with 63 samples (42.00%), compared to Modified Giemsa, the most dominant density score of Grade 1 (mild) with 61 samples (40.70%). Conclusion: Warthin-Starry detects more H. pylori compared to Modified Giemsa. Additionally, the Warthin-Starry yields higher Density Grading using the Updated Sydney System for Grade 2 (Moderate) compared to the Modified Giemsa, with a dominant grade at Grade 1 (Mild) in chronic gastritis. This highlights the importance of selecting the most appropriate histochemical staining method for accurate early diagnosis, where resource limitations restrict the use of advanced diagnostic modalities that may not be routinely available.